Karyotype Analysis in Five Species of Carthamus L. (Asteraceae) from Iran - Atefeh Aghakoochaki; Maneezheh Pakravan (Journal of Genetic Resources)
The genus Carthamus, a member of the family Asteraceae, includes about 25 species worldwide and 7 species in Iran. In this study, chromosome numbers and karyotypes of 13 populations of five species of the genus Carthamus (Asteraceae family) were investigated. Also, the pollen sterility percentage was calculated for each species. The findings confirmed the triploid chromosome numbers for two species, C. tinctorius and C. dentatus, respectively with 24 and 20 chromosomes, aligning with previous reports. C. lanatus was identified as a polyploid with 44 chromosomes. Additionally, one population of C. dentatus was recognized as a triploid with 30 chromosomes as a first-time report. Among the three populations of C. turkestanicus studied, two populations confirmed the previously reported allopolyploid with 64 chromosomes, while one exhibited a new finding of 60 chromosomes. Karyotype analyses revealed that all populations possess asymmetrical karyotypes. The karyotype formulas were as follow: 4m+ 5sm+ 2st+ t for C. tinctorius (2n= 2x= 24), M+ 19m+ 2Sm for C. lanatus, M+ 7m+ 2sm for C. dentatus (2n= 2x= 20), M+7m+2Sm for the population of C. dentatus with 2n= 30, and M+ 17m+ 13sm+ T for C. turkestanicus (2n= 64).  A cluster analysis by Ward method has separated the diploid and polyploids species. These karyological data significantly enhance our understanding of Carthamus and will prove to be a valuable resource for future research on this genus.